Use Of GPS And GIS For Preparation Of Input Maps For AGNPS Model Based On Elevation - Wong, Kok Foo (Universiti Sains Malaysia, 2005)
Agricultural Non-Point Source (AGNPS) is a distributed parameter model that predicts soil erosion and nutrient transport from agricultural watersheds for real or hypothetical storms. Erosion modeling is built upon the Universal Soil Loss Equation (USLE), which predicts the long term average annual rate of erosion on a field slope based on rainfall pattern, soil type, topography, crop system and management practices. The determination of slope and its corresponding slope length is identified by slope and aspect classes. In the present study, elevations of about 500 well-distributed points were taken by using Global Positioning System (GPS). Root Mean Square Error (RMSE) of these elevations was determined by comparing the elevation interplolated from the contours. By combining the elevation of points and the contour maps, a Digital Elevation Model (DEM) was created by using Geographical Information System (GIS). From the DEM, various parameters such as flow direction, flow accumulation, watershed area, slope, aspect, hillshade and LS factor map was produced. Flow direction is determined by finding the steepest descent from each cell while flow accumulation represent the amount of rain that would flow through each cell, assuming that all rain become runoff. The watershed areas are described as the surface runoff as being the locus of points within an area where runoff produced inside the parameter will move into a single watershed outlet. Slope, aspect and hillshade are useful in determining the LS factor. A detailed analysis for determination of LS factor is carried out using the AGNPS – GIS interface. Results shows that the values of LS factor vary from 0 – 111.